Constraints-led approach to coaching the power clean - Verhoeff, W.; Millar, S.-K.; Oldam, T. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to apply a constraints-led approach to the acquisition of the power clean. Strength and conditioning coaches need to coach complex motor skills, where the common method involves explicit instruction and task decomposition. However, contemporary skill acquisition theory is in conflict with this explicit and reductionist approach. Through three case studies the examination of individualised task constraints were used to allow a self-organization process to skill development to take place. The constraints employed for the all three case studies achieved movement change in the predicted direction. In two of the three cases, the movement changes resulted in performance improvements measured through 1RM. In conclusion, the constraints-led approach was an effective method for changing movement behaviour in the context of strength and conditioning.